Incidence of Positive Ventricular Late Potentials Differs in Postural Changes among Supine, Left, and Right Lateral Decubitus, and Prone and Sitting Positions in Brugada Syndrome - Yoshioka, Koichiro (Ann Noninvasive Electrocardiol, 2014)
BACKGROUND: High‐risk patients with Brugada syndrome (BrS) have inherent late potential (LP) fluctuations that might be explained by autonomic activity, electrolyte abnormality, and body temperature changes. However, the correlation between postural changes and LP determinates remains unknown. METHODS: Forty patients with BrS (38 men, 43.9 ± 13.5 years) and 15 controls (15 men, 42.4 ± 11.2 years) were enrolled. LP variations were investigated at five body positions using high‐resolution ambulatory monitoring electrocardiography (HR‐ambulatory ECG). The HR‐ambulatory ECG was recorded for 3 hours and LP parameters (fQRSd, LAS40, and RMS40) were obtained for at least 15 minutes in each at the supine, left and right lateral decubitus, and prone and sitting positions. RESULTS: Determinate LP in the BrS group was significantly abnormal in all positions. Among the five body positions, positive LP were much more frequent in the supine and left and right lateral decubitus positions than in the prone and sitting positions and normalized in the last two positions in patients with BrS. RMS40 variance by postural change was significantly larger in the coved group than in the saddle back group. Determinate LP improved in the sitting position compared to the supine position in the coved group. CONCLUSIONS: Positive LP findings normalized in the sitting position in patients in the coved BrS group with a resuscitation history, suggesting that depolarization instability might be related to the risk of fatal ventricular arrhythmia. Posture‐induced LP variance should be examined using HR‐ambulatory ECG analysis in patients with BrS.